Avaliação da focalização e do impacto do Programa Mais Médicos no Brasil sobre indicadores selecionados - Machado, Luciana Paixão Maciel (2020)
Between 2013 and 2018, the ratio of doctors per thousand inhabitants in Brazil went from approximately 2.0 professionals per thousand inhabitants to 2.18. This was the highest rate of doctors so far, ever recorded in the country. The increase observed was due to the More Doctors Program, instituted by the Government in July 2013 in an attempt to resolve the emergency issue of basic care and create conditions for the training of new doctors. However, the improvement in numbers did not guarantee a better distribution of these professionals in the regions of the country. Within this scope, this research aimed to examine the impacts caused by the More Doctors Program in its initial two years of operation and to conduct a focus study to examine whether the Program prioritized the sending of doctors to regions of greatest need, as proposed. The results obtained in the focus analysis indicated that the PMM ended up prioritizing municipalities with ratios greater than 1 doctor from the SUS per thousand inhabitants and with comparatively lower proportions of the population in extreme poverty. The analysis of impact indicators showed that the PMM had no effect on the percentage of primary care admissions or on the number of medical consultations held in the country.